A History of World Societies since 1450 : volume 2 - Wiesner, Merry E.; Ebrey, Patricia Buckley; Beck, Roger B.; Dávila, Jerry; Crowston, Clare Haru; MacKay, John P. (Bedford/Saint Martin's, 2019)
Take the lead in succeeding in your history course -- Avoiding Plagiarism and Managing Sources -- About the Cover Image -- Maps -- Half-title Page -- Title Page -- Copyright Page -- Preface -- Versions and Supplements -- Brief Contents -- Contents -- Maps, Figures, and Tables -- Introduction: The Origins of Modern World Societies -- Chapter 16: The Acceleration of Global Contact, 1450-1600 -- The Afroeurasian Trade World -- The Trade World of the Indian Ocean -- Peoples and Cultures of the Indian Ocean -- Trade with Africa and the Middle East -- Genoese and Venetian Middlemen -- The European Voyages of Discovery -- Causes of European Expansion -- Technology and the Rise of Exploration -- The Portuguese in Africa and Asia -- Spain's Voyages to the Americas -- Spain "Discovers" the Pacific -- Early Exploration by Northern European Powers -- Conquest and Settlement -- Spanish Conquest of the Aztec and Inca Empires -- Portuguese Brazil -- Colonial Administration -- Indigenous Population Loss and Economic Exploitation -- Patterns of Settlement -- The Era of Global Contact -- The Columbian Exchange -- Sugar and Early Transatlantic Slavery -- Spanish Silver and Its Economic Effects -- The Birth of the Global Economy -- Changing Attitudes and Beliefs -- Religious Conversion -- European Debates About Indigenous Peoples -- New Ideas About Race -- Chapter Summary -- Connections -- Chapter 16 Review -- Chapter 17: The Islamic World Powers, 1300-1800 -- The Turkish Ruling Houses: The Ottomans, Safavids, and Mughals -- The Expansion of the Ottoman Empire -- The Ottoman Empire's Use of Slaves -- The Safavid Empire in Persia -- The Mughal Empire in India -- Cultural Flowering -- The Arts -- City and Palace Building -- Gardens -- Intellectual Advances and Religious Trends -- Coffeehouses and Their Social Impact -- Non-Muslims Under Muslim Rule.